Design of Hypothetical Learning Trajectory (HLT) in Mathematics using motif of Anyaman Bambu - Suparman; Maryati (Asian Journal of Assessment in Teaching and Learning, 2019)
Several previous researches showed that students had difficulty in understanding the concept of transformation. Students are more likely to be introduced by using formula, and their learning is separate from the daily experience of students. This underlies the researcher to design a learning trajectory of learning transformation and to connect it with experience-based activities. The purpose of this research is to design of hypothetical learning trajectory in learning translation using motif of Anyaman Bambu as a starting point or learning context. The method used in this research is design research with three-step that is preliminary design, design experiment, and retrospective analysis. The subjects in this research were several samples of student’s class VIII junior high school. The results of this research is the design of hypothetical learning trajectory in learning translation using the motif of Anyaman Bambu with a learning trajectory that is student drawing motif of Anyaman Bambu freely, student drawing motif of Anyaman Bambu with agreed conditions, student record the starting point and endpoint of the translation results in activities drawing the motif of Anyaman Bambu and finding the relationship between the two and finally, the student found the translation formula.